Ethics and corporate social responsibility on the food market - Košútová, Tatiana; Jarossová, Malgorzata A. (Engineering Sciences And Technologies, 2014)
Ethics is an essential and integral part of social responsibility. Corporate Social Responsibility (CSR) can be seen as the responsibility of businesses towards society and the environment for the consequences of their decisions and carried out activities. A characteristic feature of the CSR is that companies’ behaviour is consistent with ethical behaviour, legislation and international standards of behaviour. Ethical behaviour, which deals with business ethics, is in fact the result of the solution to the conflict between the individual interests of businesses and interests of stakeholders. Consumers are a particular group of stakeholders which are interested in ethical behaviour and social responsibility of companies on the food market
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2014, Nr 3 (14), s. 34-50
Keywords: ethics; corporate social responsibility; food; RASFF; consumer; etyka; CSR; żywność; konsument